Analysis of the Influence of Economic and Social Infrastructure on Economic Growth in East Java - Muchamad Toha Yudo Pratama; M Taufiq (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study aims to determine the effect of economic and social infrastructure on economic growth in East Java in the 2008-2022 period. This research approach uses a quantitative approach. By using independent variables, namely the electricity infrastructure variable, the road infrastructure variable, the health infrastructure variable, and the education infrastructure variable and the dependent variable is the economic growth variable. The data analysis technique uses multiple linear regression analysis with the Ordinary Least Square (OLS) model with IBM SPSS 21 as the data processor. The results of my research studies show that electricity, health, and education infrastructure have a positive and significant impact on economic growth, while road infrastructure does not affect economic growth.